2011
DOI: 10.1088/1748-6041/6/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical properties of enamel after microabrasion, polishing, and storage in artificial saliva

Abstract: This study evaluated the effect of microabrasion and polishing on the microhardness and roughness of bovine enamel, and the effect of artificial saliva on the hardness of enamel. Bovine enamel blocks were used, forming the groups (n = 48): GI-37% phosphoric acid and pumice, GII--Opalustre, and GIII--Whiteness RM. The groups were divided into different subgroups: (a) diamond paste, (b) fluoride prophylactic paste, and (c) without polishing. Hardness tests were carried out at the following set times: (T1) initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 9 publications
3
38
0
6
Order By: Relevance
“…Remineralization of the in vitro specimens was not sufficient to restore the tooth enamel, a result in accordance to that reported by Fragoso et al 15) . The interaction of HS with the components of the microabrasive product seems to be significant with respect to its remineralizing action on microabraided enamel.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Remineralization of the in vitro specimens was not sufficient to restore the tooth enamel, a result in accordance to that reported by Fragoso et al 15) . The interaction of HS with the components of the microabrasive product seems to be significant with respect to its remineralizing action on microabraided enamel.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained from the quantitative analyzes in this present study are confirmed by the qualitative analysis using scanning electron microscopy, confirming the values found for hardness and surface roughness. Signs of demineralization and surface irregularities, which are characteristic of the erosive/ abrasive action of the microabrasive 15) , were noted in the images of the groups that received microabrasion. No surface morphology changes were observed when only the bleaching agent was applied, indicating that the SEM images were in agreement with the results of the surface roughness and microhardness tests that were used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This "abrosion effect" (abrasion plus erosion) may be due to the compaction of minerals resulting from the simultaneous erosive and abrasive action of the microabrasion compound on the dental enamel 11,17 . Fragoso, et al 18 (2011) after evaluating different techniques, concluded that microabrasion followed by polishing with diamond paste or fluoride prophylatic paste provided higher hardness and better surface smoothness of the enamel 18 . In 1997, Segura, et al 33 , through an in vitro polarized microscopic study, showed that enamel after microabrasion technique is more resistant to demineralization than untreated enamel surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…A rough surface facilitates plaque retention and adhesion of microorganisms by reducing the efficacy of mastication and mechanical cleaning processes. As such, we are seeing an increasing number of studies investigating factors that modify the surface roughness of teeth in the past recent years [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%